Early American Writing - Gunn G. (New York: Pengium books, 1994)
In the literature of early American writers there is one common trait among all the writings: religion. Among Anne Bradstreet and Jonathan Edwards all speak of their opinion of religion, god, heaven, and material things.
Inv.: (NP(B/12293s
Keywords: Thomas More -- Amerigo Vespucci -- Samuel Sewall